Transcranial Approach for Venous Embolization of Dural Arteriovenous Fistula - Lívio Pereira de Macêdo; Francisco Ranilson Alves Silva; Marcos Alcino Soares Siqueira Marques Junior; Daniel Duarte Rolim; Sildomar Queiroz; Renata Raizza Monterazzo Cysneiros; Ubiratan Alves Viturino da Silva; José Laércio Júnior Silva; Gustavo Andrade; Nivaldo S. Almeida; Hildo Rocha Cirne Azevedo-Filho (Brazilian Neurosurgery)
Transvenous embolization emerges as a viable intervention for addressing intracranial dural arteriovenous fistulas (DAVF). Accessibility to the fistulous site via the internal jugular vein (IJV) may be impeded by associated dural sinus apoplexy or thrombosis, prompting the development of a transcranial approach for venous embolization in such scenarios. The presented case details the utilization of a transcranial approach for venous embolization of DAVF. This method allows unobstructed entry to DAVFs situated on superficial dural sinuses that lie beyond the reach of the IJVs. The efficacy of this approach parallels that of the conventional retrograde venous methodology. The precise location and appropriate extent of the craniectomy play pivotal roles in ensuring the success of this technique.